Studi Deskriptif Karya Seni Ecoprint Dengan Teknik Steaming Pada P5 Kelas V SDN 44 Kota Bengkulu - Sari, Mayang Sukma Permata; Yusnia (JURIDIKDAS, 2025)
This study aims to describe the results of ecoprint art using the steaming technique in class V of Elementary School 44 in Bengkulu City. This type of research is qualitative research with descriptive methods. The subjects in this study were students of class V A of Elementary School 44 in Bengkulu City. And described four works that had been made by four groups. Data collection techniques include observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and conclusion. Data validity in this study was determined through triangulation and member checks. The results of this study, namely the work that has been produced by each group, have elements of point, line, field, color, texture, light, dark, and space, but in the work of group 3, the point element has not been seen. As well as the principles of fine art, namely rhythm, balance, unity, center of attention, harmony, and proportion. It can be concluded that the works produced by each group have the elements and principles of fine art.